Covid-19 and poverty assessment in Nigeria – the vulnerability approach (2021)
Poverty alleviation has long been recognized as the implicit objective of national development in Nigeria. Indeed, successive governments in Nigeria has tinkered with different poverty alleviation measures since the early 1980s. Despite these concerted efforts by successive regimes in Nigeria, poverty has defied resolution. If any, poverty has been compounded by the current coronavirus pandemic, which has worsened the fate of the poor in Nigeria. Using analytical technique that is grounded on vulnerability theory, the study showed how the methodology of vulnerability can be applied to yield policy-relevant insights about the poverty dynamics in Nigeria and how the concept can be applied to predict the vulnerability of the poor in the country to the current coronavirus pandemic and future anthropogenic shocks.